Requirements for BIM implementation in AEC companies: a Brazilian case study - Wanderley, Ayanna Karina de Assis Santos; Lordsleem Júnior, Alberto Casado; Aquino Rocha, Joaquin Humberto (Revista de la Construcción. Journal of Construction, 2023)
Building Information Modeling (BIM) is widespread in many countries; however, its implementation still encounters some barriers in Brazil. In addition, during the BIM implementation process, some companies give up because they do not achieve the expected result. In the Metropolitan Region of Recife, adherence to the BIM methodology is less than 5% of the research universe, which is 445 among companies and professionals. This study evaluates the fulfillment of the necessary requirements for BIM implementation at Brazilian architecture, engineering, and construction (AEC) companies. The methodology was carried out using case studies and its strategy was based on the following steps: identification of the state-of-the-art and of requirements for BIM implementation, which allowed the determination of the criteria for evaluating the companies studied; the criteria determined were use to elaborate an online form for identification of AEC companies in Recife (Brazil) and a questionnaire for conducting interviews with the selected companies; subsequently, case studies were developed, and data analysis. The case studies were carried out at five AEC companies which had a median fulfilment of requirements of 65%. Many of the companies presented BIM 1.0 characteristics. It has been verified that the BIM implementation is more effective at companies where a greater number of BIM requirements are applied. The companies with the fewest requirements applied, or those that did not meet the requirements in practice, did not present significant advances in BIM implementation. The main research contributions were the compilation of the requirements for BIM implementation. Therefore, this study produces knowledge that can assist companies in the AEC industry experiencing similar difficulties in BIM implementation as those described in this paper.